Peningkatan Hasil Belajar Matematika Siswa Kelas V dalam Operasi Hitung Bilangan Bulat dengan Menggunakan Media Kartu Pasangan Warna di SDN. No. 040/XI Koto Limau Manis - Elmiati Elmiati (Universitas Batanghari Jambi, 2018)
This classroom action research was conducted to improve students' learning outcomes in mathematic subject, especially on the subject matter of integer counting using the color pair card media. This research was conducted for six months from June to November of 2016. This research involves all fifth grade students year 2016/2017 at SDN No.040/XI Koto Limau Manis which are 15 students. This research activity is carried out in two cycles. Each cycle consists of two meetings and four activities namely planning, implementation, observation, and reflection. Evaluation of student learning outcomes using test and observation. The data that have been collected is analyzed by descriptive analysis and simple statistical test. The results showed that the use of media allows students to understand math lessons, especially material counting integer operations. In addition, the use of media also makes students feel happy and eager to learn, as well as increasing the courage of students to appear in front of the class. Improvement also occurs in terms of student learning outcomes. The average grade value that initially 44 increased to 70 after the implementation of cycle I and again increased to 76 after the implementation of cycle II. The average grade value after the given action is higher than the value at which action has not been given. Student learning mastery also increased from 33.3% (pratindakan) to 80.0% (cycle I) and 93.0% (cycle II).